Forgotten Fun: Recollecting the Working-Class Pleasurescape of Hamburg's East End, 1880s-1950s. (November 2022) - Just, Alina L.
In the early twentieth century, St. Pauli was not the only place in Hamburg to go to have fun. In the city's East End, a wide range of pubs, clubs, and ballrooms turned working-class quarters into a vibrant pleasurescape. Based on historical-topographic and archival research, this paper explores eastern Hamburg's forgotten pleasurescape with the aim of drawing attention to pleasure culture as a social driving force and of redressing the balance in the city's one-sided history of pleasure culture. In the course of the study, the term "pleasurescape" is more clearly nuanced and geo-spatial historical mapping further explored as a tool for urban history.